Family Medicine - Švab, Igor; Klemenc Ketiš, Zalika; Homar, Vesna (2024)
This textbook of family medicine is a crucial resource for healthcare practitioners who are responsible for providing primary care services. The importance of a textbook of family medicine lies in its ability to provide evidence-based information that can be used to guide clinical decision-making and improve patient outcomes. One of the key features of this textbook of family medicine that sets it apart from other medica! textbooks is its focus on clinical cases. This means that the textbook is structured around real-life patient scenarios that highlight the complex and multifaceted nature of primary care. By presenting cases that illustrate the various challenges and considerations involved in providing primary care services, a textbook of family medicine can help healthcare practitioners develop the skills and knowledge they need to provide effective, patient-centered care.
Keywords: family medicine; problem-based learning; primary health care; comprehensive care; person-centred care